(untitled) (Communications in Computational Physics, 2013)
Recently, it was demonstrated that implicit solvent models were capable of generating stable B-form DNA structures. Specifically, generalized Born (GB) implicit solvent models have improved regarding the solvation of conformational sampling of DNA [1, 2]. Here, we examine the performance of the GBSW and GBMV models in CHARMM for characterizing base flipping free energy profiles of undamaged and damaged DNA bases. Umbrella sampling of the base flipping process was performed for the bases cytosine, uracil and xanthine. The umbrella sampling simulations were carried-out with both explicit (TIP3P) and implicit (GB) solvent in order to establish the impact of the solvent model on base flipping. Overall, base flipping potential of mean force (PMF) profiles generated with GB solvent resulted in a greater free energy difference of flipping than profiles generated with TIP3P. One of the significant differences between implicit and explicit solvent models is the approximation of solute-solvent interactions in implicit solvent models. We calculated electrostatic interaction energies between explicit water molecules and the base targeted for flipping. These interaction energies were calculated over the base flipping reaction coordinate to illustrate the stabilizing effect of the explicit water molecules on the flipped-out state. It is known that nucleic base pair hydrogen bonds also influenced the free energy of flipping since these favorable interactions must be broken in order for a base to flip-out of the helix. The Watson-Crick base pair hydrogen bond fractions were calculated over the umbrella sampling simulation windows in order to determine the effect of base pair interactions on the base flipping free energy. It is shown that interaction energies between the flipping base and explicit water molecules are responsible for the lower base flipping free energy difference in the explicit solvent PMF profiles.